Superb Microvascular Imaging in the Evaluation of Pediatric Graves Disease and Hashimoto Thyroiditis. (9th November 2019) - Bayramoglu, Zuhal; Kandemirli, Sedat Giray; Akyol Sarı, Zeynep Nur; Kardelen, Aslı Derya; Poyrazoglu, Sukran; Bas, Firdevs; Darendeliler, Feyza; Adaletli, Ibrahim
Abstract : Objectives: We aimed to investigate the differences between spectral Doppler and Superb Microvascular Imaging (SMI; Canon Medical Systems, Tokyo, Japan) findings in children with Hashimoto thyroiditis (HT) and Graves disease (GD) compared to healthy control participants. Methods: The study included 34 patients with GD, 37 patients with HT, and 22 healthy volunteers. All patients with HT and 11 patients with GD were euthyroid; 23 patients with GD had symptoms of hyperthyroidism and had thyrotropin values of less than 0.5 mIU/L. Thyroid volumes, mean resistive indices, and peak systolic velocities along with vascularity indices (VIs) on Superb Microvascular Imaging were measured. Results: Patients with GD had a significantly higher mean thyroid volume ( P < .001; right lobe, 11.80 mL; left lobe, 9.10 mL) and peak systolic velocity (right, 32.5 cm/s; left, 30 cm/s) with a lower resistive index (right, 0.48%; left, 0.48%) compared to patients with HT (right, 8.78 mL, 20 cm/s, 0.55%; left, 7.41 mL, 20 cm/s, 0.55%, respectively) and also control participants (right, 4.59 mL, 15 cm/s, 0.56%; left, 3.52 mL, 15 cm/s, 0.54%). Patients with GD had a significantly higher median VI (right, 25%; left, 26%) compared to patients with HT (right, 11%; left, 13%) and control participants (right, 8%; left, 8%). When patients with GD were categorized as euthyroid and hyperthyroid based on thyrotropin levels and clinical symptoms, both euthyroid and hyperthyroid patients with GD had significantly higher thyroid volumes compared to patients with HT ( P < .001). Hyperthyroid patients with GD had higher thyroid volumes compared to euthyroid patients with GD; however, the difference failed to reach statistical significance. A significant strong positive correlation with the VI and thyrotropin receptor autoantibody levels ( r = 0.696) was found. The highest area under the curve was obtained for the right lobe VI (0.885), followed by the left lobe VI (0.872), right lobe volume (0.828), and peak systolic velocity (0.810). The optimal cutoff VI value for distinguishing between HT and GD was 17.35% with sensitivity, specificity, and diagnostic accuracy of 85.3%, 78.4%, and 81.7%, respectively. Conclusions: Superb Microvascular Imaging is a new method that can detect subtle vascularity changes with higher accuracy compared to spectral Doppler parameters in distinguishing between HT and GD.